2022
DOI: 10.7759/cureus.28085
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Location of Diffuse Large B-cell Lymphoma in the Nasal Septum

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most prevalent subtype of non-Hodgkin's lymphoma (NHL). This subtype can be present in various extranodal sites, including the brain, bones, intestines, kidneys, adrenal glands, and other soft tissues. As demonstrated in this case, one rare site of DLBCL is the nasal septum, which presents as a rapidly enlarging mass resistant to antibiotics and steroids. The definitive diagnosis for this case involved biopsy, but further workup, such as computed tomography (CT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Rare sites of extranodal DLBCL have been documented in the literature, including presentations in the scalp, testicles, bone, bladder, and nasal septum [2][3][6][7][8][9]. A recent 2022 study found that the percentages of extranodal DLBCL from years 2000-2015 at the age of 18 or greater in their search were as follows: GI tract 28.31%, nervous system 13.78%, head and neck 11.79%, skin and soft tissue 9.54%, genitourinary 7.24%, musculoskeletal 5.80%, respiratory tract 5.17%, pancreas and hepatobiliary 4.16%, endocrine organs 3.66%, heart and mediastinum 3.28%, breast 2.49%, bone marrow 2.47%, and others 2.30% [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare sites of extranodal DLBCL have been documented in the literature, including presentations in the scalp, testicles, bone, bladder, and nasal septum [2][3][6][7][8][9]. A recent 2022 study found that the percentages of extranodal DLBCL from years 2000-2015 at the age of 18 or greater in their search were as follows: GI tract 28.31%, nervous system 13.78%, head and neck 11.79%, skin and soft tissue 9.54%, genitourinary 7.24%, musculoskeletal 5.80%, respiratory tract 5.17%, pancreas and hepatobiliary 4.16%, endocrine organs 3.66%, heart and mediastinum 3.28%, breast 2.49%, bone marrow 2.47%, and others 2.30% [10].…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse large b-cell lymphoma (DLBCL) represents approximately one-third of all non-Hodgkin's lymphomas [1]; extranodal presentation on the scalp is rare [2][3]. Rare extranodal presentations documented in the literature include the scalp, testicles, bone, bladder, and nasal septum, whereas, the gastrointestinal tract is the most common extranodal site [2][3][4][5][6][7][8][9]. Skin involvement in DLBCL can occur as a primary or secondary manifestation, which can be difficult to differentiate [1,4].…”
Section: Introductionmentioning
confidence: 99%